The Invisibles - an exploration of barriers experienced in workplaces, and strategies of navigating them by autistic adults without an intellectual disability. - Andrychowicz,Patrycja Julia (2026)
This project highlights a unique positioning of adult autistic workers who need to navigate workplace environments and structures without access to disability support. The focus was to recognize and examine barriers/challenges, their impact on individuals’ wellbeing, and strategies for managing them, which allow for sustaining full-time employment. This thesis draws on theoretical frameworks from the field of disability and neurodivergence studies, critical approaches to neoliberalism, and concepts of social navigation and weak resistance. Using qualitative methods, the study is based on 10 individual in-depth interviews with autistic workers in Poland employed on a full-time basis. The findings, in line with existing literature on the topic, highlight extensive barriers in employment related to sensory issues, differing communication styles, and stigma. To manage them, interviewed autistic individuals employ varied strategies which manifest both as small, daily acts and as life-path defining decisions. With little available external support and lack of recognition, their disability and needed care are highly individualized and therefore invisible. This project contributes to the fields of disability and neurodivergence studies by highlighting the underrecognized group of “invisible” autistic people and mapping out their experiences of managing disability and full-time employment.
Keywords: autism; neurodivergence; disability; work; neoliberalism; social navigation